New record of Haematotrephus nittanyense (Zeliff ,1946) Parasitized in the respiratory system of Black-winged Stilt Himantopus himantopus and White tailed Plover Chettusia leucura birds in Thi Qar Province - Iraq - Al-Mayah, Sabeeh (University of Thi-Qar Journal of Science, 2015)
Digenetic trematode, Haematotrephus nittanyense is isolated from respiratory system of Black-winged StiltHimantopus himantopus and White-tailed Plover Chettusia Leucurus,shot in Al- Chibayish marshes , Eastern of ThiQar province from December 2012 to November 2013 .The Prevalence in those birds are 17.03 , 2.15 % respectively .Mean intensity of infection 2.8 , 1.2 respectively.. This trematode is recorded for the first time in Iraqibirds,taxonomically described and illustrated.